Characterization of new Pt(IV)–thiazole complexes: Analytical, spectral, molecular modeling and molecular docking studies and applications in two opposing pathways. (25th July 2019) - Althagafi, Ismail; El‐Metwaly, Nashwa M.; Farghaly, Thoraya
Abstract : New thiazole derivatives were synthesized and fully characterized, then coordinated with PtCl4 salt. Also, the newly synthesized Pt(IV) complexes were investigated analytically (elemental and thermogravimetric analyses), spectrally (infrared, UV–visible, mass, 1 H NMR, 13 C NMR, X‐ray diffraction) as well as theoretically (kinetics, modeling and docking). The data extracted led to the establishment of the best chemical and structural forms. Octahedral geometry was the only formula proposed for all complexes, which is favorable for d 6 systems. The molecular ion peaks from mass spectral analysis coincide with all analytical data, confirming the molecular formula proposed. X‐ray diffraction (XRD) and scanning electron microscopy (SEM) allowed discrimination of features between crystalline particles and other amorphous morphology. By applying Gaussian09 as well as HyperChem 8.2 programs, the best structural forms were obtained, as well as computed significant parameters. Computed parameters such as softness, hardness, surface area and reactivity led us towards application in two opposing pathways: tumor inhibition and oxidation activation. The catalytic oxidation for CO was conducted over PtO2, which was yielded from calcination of the most reactive complex. The success of catalytic role for synthesized PtO2 was due to its particulate size and surface morphology, which were estimated from XRD patterns and SEM images, respectively. The antitumor activity was tested versus HCT‐116 and HepG‐2 cell lines. Mild toxicity was recorded for two of the derivatives and their corresponding complexes. This degree of toxicity is more favorable in most cases, due to exclusion of serious side effects, which is coherently attached with known antitumor drugs. Abstract : The synthesis process for thiazole derivatives 5a –e .